UPAYA MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN DENGAN METODE BERMAIN FOOT AND HAND GAMES PADA ANAK KELOMPOK A PAUD YATINA PENJOR - Mahendra, Juandra Prisma; Rahayu, Fitriani (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
This study aims to improve the ability to recognize numbers in children of group A in PAUD Yatina Penjor by using the method of playing foot and hand games. The type of research that researchers use is Classroom action research. The number of subjects in this study was 15 children consisting of 7 boys and 8 girls. Researchers used observation, test, and documentation techniques in data collection. Based on the results of the study, it was obtained that through the foot and hand games method, children showed an increase in the results before the action was carried out, namely children who were completed or children who got BSH and BSB scores at the time before the action there were only 5 children with a score (33.3%) with an average score of 52, while increasing in cycle 1, namely children obtained completeness as many as 9 people with a score (60%) with an average score of 68.3. Meanwhile, in cycle II, the results were obtained that children with BSH and BSB scores increased to 13 children with a score (86.6%) with an average score of 84. It can be concluded from the results of the cycle that the foot and hand games method can improve the ability to recognize numbers in children of group A in PAUD Yatina Penjor.